New basic chromosome number in Chlorophytum borivilianum Santapau and Fernandes - Maiti, K A Geetha, Satyabrata (Journal of Spices and Aromatic Crops, 2004)
Cytological studies of Chlorophytum borivilianum revealed a new chromosome number, 2n=4x=28 and also the presence of polyploids (tetraploid and octoploid levels) in the population with a basic number of x=7.